Study of various TDMA schemes for wireless networks in the presence of deadlines and overhead. - Santivanez, C.
The objective of this paper is to determine the minimum system dropping rate (or, equivalently, dropping probability) induced by time division multiple access (TDMA) schemes supporting time-constrained applications with common maximum cell delay tolerance. Expressions are derived for the induced system dropping rate for various TDMA schemes with different overhead and the maximum number of users than can be admitted in the network without violating the maximum dropping rate constraint is determined. The system dropping rate achieved by suboptimal TDMA schemes is compared against the optimal (although ideal) TDMA scheme performance. The performance limiting factors associated with the suboptimal schemes are identified, and the magnitude of their (negative) impact is evaluated. Based on this information it is possible to point to performance improving modifications which should be pursued to the extent permitted by technological constraints. Finally, based on this derivations a network designer may choose the best TDMA scheme-among realizable variations of those considered here-to use in a particular situation
Keywords: Cellular telephony; Deadlines; Dropping probability; Maximum cell delay tolerance; Minimum system dropping rate; Optimal TDMA; Overhead; Performance improving modifications; Performance limiting factors; Suboptimal TDMA; System dropping rate; Time division multiple access; Time-constrained applications; Wireless LAN; Wireless networks